L'emprise de la grammaire Propositions épistémologiques pour une linguistique mineure - Riemer, Nick (Langages, 2021)
How can we understand the philosophy of linguistics by taking the discipline's actual theoretical pluralism as our starting point? By what criteria can grammatical research be assessed if we abandon a competitive model of theorising? Through an investigation of different areas of linguistics, this book brings to light certain hermeneutic properties of linguistic theorisation which are currently poorly understood and sometimes not even yet noticed. As a complement to these investigations, the book analyses a number of questions that arise in the "ideological" criticism of contemporary linguistics, examining the discipline's theoretical activity in light of the socio-ideological realities on which it depends, sometimes unwittingly. Uniting two approaches to linguistics that are rarely brought into dialogue, the book opens up the possibility of an alternative understanding of the complexity of the particular textual objects that are grammatical theories.